Thermodynamic and catalytic properties of Cu- and Pd- oxides over mixed γ–χ–Al2O3 for methanol dehydration toward dimethyl ether. (15th March 2019) - Armenta, M.A.; Maytorena, V.M.; Alamilla, R.G.; Valdez, R.; Olivas, A.
Abstract: The development of catalytic systems to generate alternative energies capable of replacing diesel is a great challenge. Methanol dehydration (2CH3 OH → CH3 OCH3  + H2 O) is one of the most suitable catalytic reactions to produce dimethyl ether (DME). In DME synthesis, CuO/γ–Al2 O3 based-materials showed to be catalytically active at high pressures, but these lack high performance under atmospheric conditions. In this work, we synthesized CuO/γ–χ–Al2 O3, PdO/γ–χ–Al2 O3, and CuOPdO/γ–χ–Al2 O3 by a facile impregnation method for methanol dehydration at atmospheric pressure. Catalytic results showed that the CuOPdO/γ–χ–Al2 O3 sample performed the highest activity. All catalysts reached selectivity of 100% toward DME, regardless of the reaction temperature. Remarkably, the bimetallic catalyst containing low loadings of copper and palladium retained stability during 48 h of reaction at 275 °C, and after its regeneration they showed a similar trend. The activation energies ( E a ) for the methanol dehydration using the catalyst that performed the highest catalytic activity CuOPdO/γ–χ–Al2 O3 compared with the material with the lowest catalytic activity γ–χ–Al2 O3 were obtained. The activation energy values of the γ–χ–Al2 O3 and CuOPdO/γ–χ–Al2 O3 catalysts were 112.57 kJ/mol and 45.73 kJ/mol, respectively. Graphical abstract: Image 1 Highlights: DME production by dehydration of methanol using CuO doped with Pd. CuOPdO/γ–χ–Al2 O3 reached selectivity to DME of 100% at any reaction temperature. The bimetallic catalyst presented similar stability before and after regeneration. The Ea of the CuOPdO/γ–χ–Al2 O3 was lower than the Ea value of γ–χ–Al2 O3 .